Implementation of Geographic Information System for Tourist Locations and Lodging Services in Lhokseumawe City Based on Android - Misbahul Jannah; Muthmainnah Muthmainnah; Safwandi Safwandi; Mochamad Ari Saptari; Muhammad Muhammad; Rahmad Wahyudi; Mirza Farhan (International Journal of Engineering, Science and Information Technology, 2022)
The advancement of information technology is now increasingly widespread and very rapidly growing so that it can help people to enjoy the various conveniences that have been produced by this technology. One aspect of technology currently developing rapidly is mobile technology on smartphone devices (smartphones). This android-based geographic information system application is one of the results of these technological developments, which have the benefits and uses that are needed in this day and age. So with the development of the world of technology, people prefer the way of convenience and efficiency, for example, by utilizing the sophistication of smartphones. Implementing the Geographic Information System (GIS) for tourism and lodging services in Lhokseumawe aims to build tourism applications and lodging services in Lhokseumawe based on Android and implement Google services. Maps Application Programming Interface (API) to facilitate tourists in obtaining information on mapping the location of tourist attractions and lodging, routes, and tourist support facilities in Lhokseumawe City. The method used is a waterfall process model. Implementing the Lhokseumawe Tourism Application and lodging services using Javascript programming with Android Studio, MySQL database, and maps sourced from the Google Maps API. The result is an Android-based Lhokseumawe City Tourism and lodging service application that helps make it easier for tourists to obtain information about tourist attractions, lodging, and routes from their current location to the desired tourist and lodging locations in Lhokseumawe City with the help of the Global Positioning System (GPS). Tourist information and lodging services are entirely related only to data entered into the database server. The results of this application display a list and location of tourist and lodging services as well as the shortest route to the nearest tourist or inn to the user's location point. It is also hoped that this system can be developed to produce a better system than the previous one.